2008
DOI: 10.1007/s10120-008-0475-6
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous estrogen exposure in relation to distribution of histological type and estrogen receptors in gastric adenocarcinoma

Abstract: Gastric adenocarcinoma of the intestinal type is less common in women with high endogenous estrogen exposure, indicating a preventive effect of estrogen. No differences in the distribution of ERs was found between the three estrogen exposure groups. The presence of ERbeta cx in gastric cancer warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…The other reasons may involve that higher estradiol (E2) levels in U.S. people were reported in each gender possible related to the higher BMI compared with those in Japan [41,42]. Moreover, expression rates of ER-α and -β in gastric cancer by IHC in Asian population were 0% to 22.7 % and 43.6 % to 100 %, respectively [43,44], whereas those in Western population were 36 % and 11 %, respectively [45]. These physiologic and biologic differences among gender and region may impact the protective estrogen effect in gastric cancer, and also affect the impact of the c-MET pathway on clinical outcome through the cross-talk such as the EGFR or Wnt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The other reasons may involve that higher estradiol (E2) levels in U.S. people were reported in each gender possible related to the higher BMI compared with those in Japan [41,42]. Moreover, expression rates of ER-α and -β in gastric cancer by IHC in Asian population were 0% to 22.7 % and 43.6 % to 100 %, respectively [43,44], whereas those in Western population were 36 % and 11 %, respectively [45]. These physiologic and biologic differences among gender and region may impact the protective estrogen effect in gastric cancer, and also affect the impact of the c-MET pathway on clinical outcome through the cross-talk such as the EGFR or Wnt pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Oestrogen-bound ERs bind as homodimers or heterodimers to a specific DNA sequence known as the oestrogen-responsive element (ERE), and regulate the transcription of target genes (Matthews and Gustafsson, 2003). As oestrogen is a stimulant for the initiation and promotion of breast cancer, and ERa can be expressed in gastric cancer cells, it has been suggested that the ERa pathway may have a role in the progression of gastric cancer (Harrison et al, 1989b;Wu et al, 1994;Karat et al, 1999;Takano et al, 2002;Chandanos et al, 2008). In gastric cancer, ERa expression is higher in the diffuse type than in the intestinal type (Kitaoka, 1983;Tokunaga et al, 1986;Matsui et al, 1992;Zhao et al, 2003), and oestradiol (E2) enhances gastric cancer cell proliferation in vitro (Matsui et al, 1992;Takano et al, 2002).…”
mentioning
confidence: 99%
“…Recent studies have shown conflicting results of ERα expression in gastric cancer (13,14). Moreover, when using the immunohistochemical method, the expression of ERα gastric cancer tissues showed marked variability (0-62.5%) among a number of studies (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%